Tinjauan Literatur Green Finance di Beberapa Negara - M. Faizal Rangkuti; Muammar khadafi (Yayasan Tri Edukasi Ilmiah, 2024)
This article attempts to review existing research on green finance. This report identifies important themes in the green finance literature, particularly strategies for increasing green financing; efforts to make environmentally friendly investments profitable; promoting environmentally friendly financing using technology and policy, the role of regulators and financial institutions in the environmentally friendly finance agenda, and the challenges of environmentally friendly financing. Several cross-country observations regarding environmentally friendly finance challenges and solutions to green finance problems have been documented. Existing findings show that green finance has the potential to make a significant difference to the environment, society and climate change mitigation, but there are still many challenges faced such as a lack of awareness about environmentally friendly finance, inconsistent definitions of finance. environmentally friendly, lack of policy coordination for environmentally friendly financing, inconsistent policies, and lack of profitable incentives for investors and financial institutions who want to invest in climate change mitigation.